Efeito repelente do substrato de descarte de formigas cortadeiras - Mecenas, Hosana Haum Barros (2019)
The nest refuse produced by leaf-cutting ants is composed of their fungus symbiont, debris of plant material and corpses of ants, and may harbor substances and microorganisms harmful to them and their symbiont fungus, with a higher risk of mortality of workers working at the disposal and thus avoiding contact with this residue to try to reduce the risk of contamination in the colonies. In this way, studies suggest that the disposal substrate can be used to prevent the attack of leaf-cutting ants on plants. We analyzed experimentally if this repellent effect of the nest refuse is conserved in a liquid solution. For this, 30 colonies of Acromyrmex balzani and 36 colonies of Atta opaciceps in the field were selected and 30 baits made with straws and empanadas in citrus pulp were offered to each colony, being three treatments with 10 baits for each. The treatments were: 1 - "Cont" control composed of white baits soaked in 50% water / alcohol solution, 2 - "ExtAc" with pink baits soaked in extract with a concentration of 20% w / v of the A. balzani nest refuse and 3 - "ExtAt" composed of blue baits embedded in 20% w / v extract prepared with the A. opaciceps nest refuse. The baits were available to the colonies of A. balzani for 30 minutes and to the colonies of A. opaciceps for 20 minutes, counting the time and the amount of baits removed, compared through survival analysis and LME. The results indicated that there was a repellent effect on the foraging activity of the ants, and the intraspecific response was higher than the interspecific response for Atta colonies, that is, the repellency was higher with the ExtAt treatment. The ExtAt treatment also had greater efficiency with the colonies of Acromyrmex. However, for both species, the extract from colonies of another species had a significantly higher repellent effect than the control extract. Future studies are necessary to verify if extracts sprayed on leaves under field conditions have the same effect as that observed in baits and the duration of this effect under field conditions.